War journal of the second Russian Fortress Artillery Regiment of Erzéroum from its formation until the recapture of Erzeroum by the Ottoman army March 12th. 1918 ; Notes of superior Russian officer on the atrocities at Erzeroum - Tverdohlebov, Vladimir Nikolaeviç, 1876-1954.‏. ([y.y.])
36, 12, 37, 12 s.